PENGEMBANGAN MODUL PEMBELAJARAN BIOLOGI TERINTEGRASI AL-QUR’AN PADA MATERI BIOTEKNOLOGI - Wina Ulfa Aulia; Khairuddin Khairuddin; Rasyidah Rasyidah (JOURNAL SCIENTIFIC OF MANDALIKA (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2023)
This study aims to determine the process of developing an integrated Al-Qur'an biology learning module on biotechnology material as an alternative teaching material and to determine the feasibility of developing an Al-Qur'an integrated biology learning module on biotechnology material as an alternative teaching material. The learning module development design uses the Borg & Gall model with 7 stages of development. The Al-Qur'an integrated Biology learning module on biotechnology material was assessed by 1 material expert validator, 1 media expert validator, 1 Islamic religious expert validator, 1 teacher and 32 students from Madrasah Aliyah Swasta Al Manar Pulau Raja. The data collection instrument used a questionnaire. Data analysis was descriptive qualitative and quantitative. The results obtained indicate that the development of the Al-Qur'an integrated biotechnology learning module received a good response and received a very satisfactory response by biology teachers with a total percentage of teacher assessments being 97.5% with Very Eligible/Very Valid criteria and from the assessment the total number of students from the large group test was 90.8% with the criteria of Very Eligible/Very Valid and the small group test of 88% with the criteria of Very Eligible/Very Valid. Thus, this module is declared very feasible/very interesting to be used as teaching material in biology learning in class XII IPA Madrasah Aliyah. Thus, it can be concluded that the Al-Qur'an integrated Biology learning module on Biotechnology material which was developed with the Borg & Gall model, is Eligible and Very Interesting to be used as teaching material for students in class XII MA, especially on Biotechnology material.